Telescopic overdenture in mandibular class III kennedy - Dammar, Irfan; Mude, Acing H.; Ikbal, Muhammad; Baso, Maharani K. (Journal of Case Reports in Dental Medicine, 2020)
Objective: Overdenture with retained precision attachment helps in distribution of masticatory forces, minimize trauma to abutments and soft tissue, minimize the ridge resorption, improve the esthetics and maintain the proprioception. When it is difficult to find a suitable path of insertion because unparallel abutment teeth, telescopic crown indicated.Methods: A 66-years-old female patient visited Dental Hospital Hasanuddin University with mastication and aesthetic problems so that she wanted to make a denture. Patient had missing teeth as in 35 36 37 45 46 and 47, indicated for the fabrication of overdenture with telescopic crown in teeth 34 38 44 and 48. Fabrication of telescopic crown began by making of study model with preliminary bite record. Full crown preparation has done on teeth 34 38 44 and 48, and impression for fabrication of primer coping and metal framework with double impression technique. Primary coping has cemented on the abutment teeth, then reimpression. Secondary coping soldered with base metal framework denture was tried in the patient. Next, the determination of DVO, artificial teeth was arranged and tried to the patient, next processed the denture with acrylic and inserted it.Â Results: Precision attachment that used in this case is a telescopic crown, which consists of 2 types of crowns, the primary crown that is permanently attached to the supporting tooth, and the secondary crown attached to the denture.Â Conclusion: Many studies have done, and can concluded that telescopic overdenture is a unique and retentive type of prosthodontic treatment.